Pterocarpus santalinus Selectively Inhibits a Subset of Pro-Inflammatory Genes in Interleukin-1 Stimulated Endothelial Cells - Natalia, Priscilla; Zwirchmayr, Julia; Rudžionytė, Ieva; Pulsinger, Alexandra; Breuss, Johannes M.; Uhrin, Pavel; Rollinger, Judith M.; de Martin, Rainer (Frontiers in Pharmacology, 2022)
Based on the traditional use and scientific reports on the anti-inflammatory potential of red sandalwood, i.e., the heartwood of Pterocarpus santalinus L., we investigated its activity in a model of IL-1 stimulated endothelial cells. Endothelial cells were stimulated with IL-1 with or without prior incubation with a defined sandalwoodextract (PS), and analyzed for the expression of selected pro-inflammatory genes. The activity of NF-kB, a transcription factor of central importance for inflammatory gene expression was assessed by reporter gene analysis, Western blotting of IkBa, and nuclear translocation studies. In addition, microarray studies were performed followed by verification of selected genes by qPCR and supplemented by bioinformatics analysis. Our results show that PS is able to suppress the induction of E-selectin and VCAM-1, molecules that mediate key steps in the adhesion of leukocytes to the endothelium. It also suppressed the activity of an NF-kB reporter, IkBa phosphorylation and degradation, and the nuclear translocation of NF-kB RelA. In contrast, it stimulated JNK phosphorylation indicating the activation of the JNK signaling pathway. Gene expression profiling revealed that PS inhibits only a specific subset of IL-1 induced genes, while others remain unaffected. Most strongly suppressed genes were the signal transducer TRAF1 and the chemokine CX3CL1, whereas IL-8 was an example of a non-affected gene. Notably, PS also stimulated the expression of certain genes, including ones with negative regulatory function, e.g., members of the NR4A family, the mRNA destabilizing protein TTP as well as the transcription factors ATF3 and BHLHB40. These results provide mechanistic insight into the anti-inflammatory activity of PS, and suggest that it acts through the interplay of negative and positive regulators to achieve a differential inhibition of inflammatory gene expression.